The Role of Telemedicine as Health Promotion Media during the Covid-19 Pandemic in Indonesia: A Systematic Review - Made Karma Maha Wirajaya; Vitalia Fina Carla Rettobjaan (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: WHO has declared COVID-19 as a worldwide pandemic in March 2020, which has prompted several countries to take steps to prevent its spread due to the increasing number of cases. One of the policies implemented in Indonesia is the PSBB, so it has an impact on all aspects including access to health services. The rapid development of information technology in the era of the industrial revolution 4.0 has a positive impact, especially for the effectiveness and efficiency of health services, namely the development of e-health which is one component to bring health services closer to the community, one of which is in the form of telemedicine. This study aims to describe the role of telemedicine as health promotion media during the current COVID-19 pandemic. Methods: This research used a literature study approach. This study used 6 reviewed articles. The data was extracted by determining the key variables and then analyzed descriptively which is presented in tabular form. Results: Telemedicine is widely used as a medium of health communication by the public. One of the reasons people use telemedicine in health communication at this time is that the COVID-19 pandemic condition makes patients too afraid and anxious to conduct face-to-face consultations and visit hospitals. Besides that, telemental Counseling on Reducing Adolescent Anxiety Due to Exposure to Covid 19 Information. In addition, telemedicine can also be applied in the field of nutrition in the implementation of nutritional care in hospitals. Conclusion: Telemedicine as a health promotion media can be utilized in various fields such as telegize, telemedicine in midwifery and emergency room, telemental, and telepsychology.